PLANT DIVERSITY IN THE FOREST ECOSYSTEM OF CARRANGLAN WATERSHED, NUEVA ECIJA, PHILIPPINES - Paz-Alberto, Annie Melinda; Serrano, Shirly C.; Galvez, Cecilia T.; Gojo Cruz, Paul Henric P. (Silliman Journal, 2022)
Forests are home to 50-90% of the Earth’s species providing food, wood, fiber, energy, raw materials, industrial chemicals, and medicine. Biodiversity is a vital part of the earth’s capital, preserving the plant’s genes, species, and ecosystems hence, biodiversity conservation should be a priority. This study assessed plant diversity in Carranglan, Nueva Ecija, Philippines to determine the exploitation and conservation status of its forest ecosystem. Plants were collected, preserved, described, identified and classified. The number and distribution of each species of plants were noted for diversity assessment. Data were gathered using quadrat sampling method with ten pre-selected stations: five were located at Barangay Gen. Luna and five were at Barangay Burgos. There were a total of 292 different plant species in the area, under 91 families with families Moraceae, Myrtaceae, Araceae, and Rubiaceae as most represented. Trees, shrubs and vines are the most common, with some ferns, mosses, herbs, grasses, sedges, and epiphytes. Shannon’s Diversity Index showed that the study areas exhibited very high diversity. There were 25 plants found to have been part of the International Union for the Conservation of Nature (IUCN) Red List of 2013. Four species of these belonging to the genus Shorea were listed as critically endangered, two of which are endemic to the Philippines. Near threatened, endangered, threatened, vulnerable, and plant of least concern were recorded. Twenty four endemic plants, 15 introduced plant species and four invasive plant species were also recorded. Three species, namely Oncosperma. horridum (Griff.) Scheff., Dinochloa luconiae (Munro) Merr. and Radermachera gigantea (Blume) Miq. could serve as potential biodiversity indicator species in both of the study areas due to their high number of individuals, frequency, and abundance. Threats to the Carranglan Forest ecosystem include fires, timber poaching, kaingin practices, soil erosion, and small-scale mining.